Serum Levels of Fibroblast Growth Factor 19 Correlate with the Severity of Diarrhea and Independently from Intestinal Inflammation in Patients with Inflammatory Bowel Disease or Microscopic Colitis - Lyutakov, Ivan; Nakov, Radislav; Valkov, Hristo; Vatcheva-Dobrevska, Rositsa; Vladimirov, Borislav; Penchev, Plamen (Turkish Journal of Gastroenterology, 2021)
Background: In chronic diarrhea patients, massive over-reporting symptom-based criteria for functional bowel disorders are pitfalls. There is currently no objective biomarker that may provide a correct correlation with the severity of chronic diarrhea. To clarify the role of fibroblast growth factor-19 (FGF-19) as a biomarker of objective measurements of the severity of diarrhea in comparison with a patientreported outcome, based on the Bristol Stool Form (BSF) Scale. Methods: Consecutive 100 patients with chronic diarrhea underwent standard investigations with laboratory tests, fecal calprotectin (FC), endoscopy with biopsies, and serum FGF-19. All patients and 14 healthy controls completed a diary recording, BSF, and stool frequency. Results: We found that irritable bowel syndrome with diarrhea (IBS-D) n = 21/23 (91%) reported a high number on BSF ≥6, compared to patients with inflammatory bowel diseases (IBD) 56/77 (72%) with BSF ≥ 6 (P = .011). FGF-19 median serum levels were significantly lower in Microscopic colitis (0.010 pg/mL) and IBD patients (0.009 pg/mL) compare to IBS-D (266.9 pg/mL) and high levels in healthy subjects (463 pg/mL) (P < .001). Strong inverse correlation of FGF-19 with the stool frequency/day and stool index was found (r = −0.800, P < .001; r = −0.739, P < .001), independently from disease activity (r = −0.718, P = .001; r = −0.792, P = .001). Conclusion: Serum FGF-19 can become a new biomarker for evaluating the severity of diarrhea with objectively and independently from intestinal inflammation. FC and FGF-19 are predictive biomarkers for the organic cause of diarrhea.